2012
DOI: 10.1024/1421-0185/a000090
|View full text |Cite
|
Sign up to set email alerts
|

A Household Study of Self-Regulation in Children

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 76 publications
1
4
0
Order By: Relevance
“…In the present study, the age of the child showed a positive association with waiting time in the marshmallow test. This is consistent with previous findings of positive associations between children's age and DoG showing an increase of children's ability to delay gratification over development (Drobetz et al 2012;Houck and Lecuyer-Maus 2004). Maternal and paternal years of education were also significantly associated with children's waiting time in the models including only maternal and paternal data, respectively.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In the present study, the age of the child showed a positive association with waiting time in the marshmallow test. This is consistent with previous findings of positive associations between children's age and DoG showing an increase of children's ability to delay gratification over development (Drobetz et al 2012;Houck and Lecuyer-Maus 2004). Maternal and paternal years of education were also significantly associated with children's waiting time in the models including only maternal and paternal data, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…To our knowledge, the relationship between maternal personality and children's DoG has only been addressed in one study so far: In a sample of six-year-old school children, Drobetz et al (2012) measured maternal personality with the Big Five Inventory-SOEP (BFI-S) and DoG with the delay of gratification paradigm by Mischel et al (1989). In this sample, no associations between maternal Big Five and the children's DoG were found.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations